Validation of a new three-dimensional imaging system using comparative craniofacial anthropometry - Farhad B. Naini; Sarah Akram; Julia Kepinska; Umberto Garagiola; Fraser McDonald; David Wertheim (SpringerOpen, 2017)
Abstract Background The aim of this study is to validate a new three-dimensional craniofacial stereophotogrammetry imaging system (3dMDface) through comparison with manual facial surface anthropometry. The null hypothesis was that there is no difference between craniofacial measurements using anthropometry vs. the 3dMDface system. Methods Facial images using the new 3dMDface system were taken from six randomly selected subjects, sitting in natural head position, on six separate occasions each 1 week apart, repeated twice at each sitting. Exclusion criteria were excess facial hair, facial piercings and undergoing current dentofacial treatment. 3dMDvultus software allowed facial landmarks to be marked and measurements recorded. The same measurements were taken using manual anthropometry, using soluble eyeliner to pinpoint landmarks, and sliding and spreading callipers and measuring tape to measure distances. The setting for the investigation was a dental teaching hospital and regional (secondary and tertiary care) cleft centre. The main outcome measure was comparison of the craniofacial measurements using the two aforementioned techniques. Results The results showed good agreement between craniofacial measurements using the 3dMDface system compared with manual anthropometry. For all measurements, except chin height and labial fissure width, there was a greater variability with the manual method compared to 3D assessment. Overall, there was a significantly greater variability in manual compared with 3D assessments (p < 0.02). Conclusions The 3dMDface system is validated for craniofacial measurements.